Pelatihan Pembukuan Keuangan Sederhana Bagi UMKM Di Desa Telajung - MH Ainulyaqin; Nur’aeni; AS Rakhmat; Sakum; Sarwo Edy (DPPM Universitas Pelita Bangsa, 2023)
Determining the success of a business will be easy if you are able to separate personal funds from business funds, make financial records of purchases and sales. Unfortunately, there are still many MSME players who do not realize the importance of using financial bookkeeping and the many benefits of financial bookkeeping. This community service activity helps to provide simple financial bookkeeping training for MSMEs to increase their knowledge and skills in managing their business finances. The method used by community service is the training method. And obtained positive reactions or results from MSME actors in RT 001 RW 001 Telajung Village, West Cikarang District, Bekasi Regency because they gained new insights in the description of the delivery of material on how to manage their business through the use of simple and straightforward accounting or financial records that are easy to understand.